Implementation of Business Development and Financial Reporting in Small and Medium Micro Enterprises (SMEs) Kelvin's Tempe Chips: Perkembangan Usaha dan Penerapan Laporan Keuangan pada Usaha Menengah Kecil Mikro (UMKM) Keripik Tempe Kelvin - Dasir; Nina Sabrina (Altifani Journal: International Journal of Community Engagement, 2025)
The problems faced by UMKM Tempe Kelvin Chips as a partner are production, marketing and financial administration problems. The purpose of this service is to help solve partner problems. Through counseling, training, mentoring and providing assistance for production facilities and infrastructure provided to partners. By recording business activities and making financial reports using Si Apik, the development of the Kelvin Tempe Chips business can be seen. The results of the service obtained by partners have improved the production of “tempeh” chips, have carried out online marketing and managed financial reports with the Si Apik application.